EVALUASI KINERJA JEMBATAN INTERCHANGE BETON DENGAN ANALISIS RIWAYAT WAKTU TIDAK LINEAR - Dendi Nosya, Akhmad; Sutrisno, Adi; Farid, Mifta; Ilyas Pratama, Nuriana; Dwiyanto, Efri; Azmi, Nazril (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
One of the elements in the bridge structure is prestressed concrete. Bridge performance evaluation is needed to determine the repair method for the element if there is a potential for construction failure. This study aims to design a prestressed concrete bridge using midas Civil software. The bridge structure is modelled along with the working loads, which include Dead Load (DL), Super Impose Dead Load (SIDL), and earthquake loads based on SNI 1725:2016 and SNI 2833:2016. This study uses a non-linear time history analysis method (non-linear time history analysis), and design parameters are taken from the NCHRP 44 and 949 references. Midas Civi software is used for the analysis. Design parameters include concrete material strain, steel reinforcement, and drift on lateral retaining elements (bridge pillars) composed of reinforced concrete material. The Terbanggi Besar Interchange Bridge (IC) STA. 139+925 on the Bakauheni – Terbanggi Besar Toll Road in Lampung Province is used as the focus of the study. This study identifies the limits of bridge structural damage during the post-earthquake to determine the performance of the bridge structure. Seven pairs of ground motions were installed, representing the conditions at the bridge site. The results of this study indicate that the performance level of the Terbanggi Besar IC Bridge Structure is at the whole operational performance level. This level describes the condition after receiving the earthquake load. The bridge condition can operate optimally, and the structure is still elastic. This study suggests using similar methods on other bridges to hinder bridge performance and anticipate building failure.